Preferential X Chromosome Inactivation as a Mechanism to Explain Female Preponderance in Myasthenia Gravis - Vanessa Nicolì (Genes, 2022)
Myasthenia gravis (MG) is a neuromuscular autoimmune disease characterized by prevalence in young women (3:1). Several mechanisms proposed as explanations for gender bias, including skewed X chromosome inactivation (XCI) and dosage or sex hormones, are often involved in the development of autoimmunity. The skewed XCI pattern can lead to an unbalanced expression of some X-linked genes, as observed in several autoimmune disorders characterized by female predominance. No data are yet available regarding XCI and MG. We hypothesize that the preferential XCI pattern may contribute to the female bias observed in the onset of MG, especially among younger women. XCI analysis was performed on blood samples of 284 women between the ages of 20 and 82. XCI was tested using the Human Androgen Receptor Assay (HUMARA). XCI patterns were classified as random (XCI < 75%) and preferential (XCI ≥ 75%). In 121 informative patients, the frequency of skewed XCI patterns was 47%, significantly higher than in healthy controls (17%; p ≤ 0.00001). Interestingly, the phenomenon was observed mainly in younger patients (<45 years; p ≤ 0.00001). Furthermore, considering the XCI pattern and the other clinical characteristics of patients, no significant differences were found. In conclusion, we observed preferential XCI in MG female patients, suggesting its potential role in the aetiology of MG, as observed in other autoimmune diseases in women.